PENGUATAN LITERASI TEOLOGI PENTAKOSTA BAGI JEMAAT MELALUI SEMINAR PENGAJARAN ONLINE DI GBI RAYON 1G - Johannes Rajagukguk; Junifrius Gultom; Bertina Munthe (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2026)
This community service program aimed to strengthen Pentecostal theological literacy among the congregation of GBI Rayon 1G through an online teaching seminar entitled “Pentecost amid Various Christian Streams.” The program was motivated by the increasing exposure of congregants to diverse theological currents, digital spirituality, and interdenominational religious practices, which require stronger theological discernment. The implementation method consisted of four stages: preparation, seminar implementation, evaluation, and follow-up. The seminar was conducted online through Zoom Meeting and attended by 100 participants, including congregants, church workers, cell-group leaders, and ministry members within GBI Rayon 1G. The results show that 86 participants attended the program until the end, and 80 participants completed the evaluation form. The evaluation indicated an increase in participants’ average understanding from 54.8% before the seminar to 86% after the seminar, representing a 31.2% improvement. The highest increase was found in participants’ ability to distinguish sound teaching from deviant teaching, which improved by 34%. Participants’ responses were also highly positive, with 96.25% stating that the seminar theme was relevant to the needs of the congregation and 97.5% recommending further theological formation. Therefore, the online teaching seminar proved effective as a community service model based on theological education, strengthening doctrinal understanding, critical awareness, and the spiritual maturity of Pentecostal congregants. ABSTRAKKegiatan Pengabdian kepada Masyarakat ini bertujuan untuk memperkuat literasi teologi Pentakosta bagi jemaat GBI Rayon 1G melalui seminar pengajaran online bertema “Pentakosta di Tengah Berbagai Aliran”. Kegiatan ini dilatarbelakangi oleh meningkatnya paparan jemaat terhadap berbagai arus pengajaran, spiritualitas digital, dan praktik keagamaan lintas denominasi yang menuntut kemampuan discernment teologis. Metode pelaksanaan dilakukan melalui empat tahap, yaitu persiapan, pelaksanaan seminar, evaluasi, dan tindak lanjut. Seminar dilaksanakan secara daring melalui Zoom Meeting dan diikuti oleh 100 peserta yang terdiri atas jemaat, pelayan gereja, pemimpin kelompok sel, dan unsur pelayanan di lingkungan GBI Rayon 1G. Hasil kegiatan menunjukkan bahwa 86 peserta mengikuti kegiatan hingga selesai dan 80 peserta mengisi formulir evaluasi. Evaluasi menunjukkan peningkatan rata-rata pemahaman peserta dari 54,8% sebelum kegiatan menjadi 86% setelah kegiatan, atau mengalami kenaikan sebesar 31,2%. Peningkatan tertinggi terdapat pada kemampuan membedakan ajaran sehat dan ajaran menyimpang sebesar 34%. Respons peserta juga sangat positif, dengan 96,25% peserta menyatakan tema seminar relevan dengan kebutuhan jemaat dan 97,5% peserta menyatakan perlunya pembinaan lanjutan. Dengan demikian, seminar pengajaran online terbukti efektif sebagai model PkM berbasis edukasi teologis yang mampu memperkuat pemahaman doktrinal, kesadaran kritis, dan kedewasaan iman jemaat Pentakosta.